Experimental Study on the Dynamic Heat Transfer Characteristics of a Mechanically Pumped Two-phase Cooling Loop - Li, Lei; Tao, Jianyun; Gao, Wei (Frontiers in Energy Research, 2021)
The present research designs a mechanically pumped cooling loop system and conducts an experimental investigation on the dynamic heat transfer characteristics of the system. The effects of the start-up heat load and heat load variation on the dynamic characteristics of the system are analyzed. The results indicate that during the start-up period, as the heat load rises, the temperature overshoot and duration time of adjustment decrease, while the pressure oscillation amplitude increases. During the regular operation period, as the heat load increases, the temperature at the evaporator outlet gradually increases until it approaches the saturation temperature and then remains constant. The pressure evolution at the evaporator outlet can be divided into four stages: steady state, drastic oscillation, damped oscillation, and slight oscillation.